ChemInform Abstract: Ammonothermal Synthesis and Crystal Structure of BaAl2(NH2)8·2NH3. Issue 35 (8th August 2013) - Pust, Philipp; Schmiechen, Sebastian; Hintze, Frauke; Schnick, Wolfgang
Abstract BaAl2(NH2)8·2NH3 is synthesized from Al2Ba intermetallic phase, NH3, and Al foil as substrate under ammonothermal conditions (autoclave, 823 K, 245 MPa; 700 h).